Los mamíferos silvestres de Milpa Alta, Distrito Federal: lista actualizada y consideraciones para su conservación - Navarro-Frías, Javier; González-Ruíz, Noé; Álvarez-Castañeda, Sergio Ticul (Instituto de Ecología, A.C., 2007)
Field surveys and consults to mammal collections yield 45 native species of mammals for the Milpa Alta Delegation. Myotis thysanodes aztecus and Myotis volans amotus are recorded for the first time for the Federal District. Four species are included as threatened by the Mexican Government (Choeronycteris mexicana, Leptonycteris yerbabuenae, Cryptotis parva soricina y Romerolagus diazi). Ten percent of the genera and one fourth of the species with distribution in this region are endemic to Mexico. Mammals present in the Milpa Alta Delegation have affinity to two biogeographic regions with different conservation priorities. The northern part, which is the most affected by human activities, includes the lowlands with xerophytic scrub vegetation. The southern area, the best preserved and with the highest species richness, includes the highlands with coniferous forest. This region should be considered a wildlife refuge and the focus for fauna conservation programs on the Federal District.